Numerical studies on the swaging process of tubes with variable wall thickness for monobloc driving shafts. Issue 1 (2nd January 2018) - Lee, Jongsup; Lim, Seong-Joo; Choi, Seogou; Lee, Sangmok
Abstract: This study analyzed thickening trends of the variable cross-section tube in relation to swaging process variables to present an effective design for the tube manufacturing process. The extent of thickening was evaluated through a finite element analysis of the swaging process with varying process variables such as die shape and initial tube thickness. As a result, the amount of thickening was found to improve with decreasing diameter reduction, taper angle, and initial tube thickness.